Flipbook Learning Boosts Multimedia Students' Learning Outcomes: Quasi-Experimental Study: Pengaruh Media Pembelajaran Flipbook pada Hasil Belajar: Studi Quasi-Eksperimental pada Siswa Kelas XII Multimedia - Muhammad Fuad Bayhaki; Rahmania Sri Untari (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative quasi-experimental study aimed to investigate the effect of implementing flipbook learning media on the learning outcomes of Class XII students at SMKN 1 Bangil. Two groups of students were assigned to either the experimental group, which utilized flipbook learning media, or the control group, which followed conventional teaching methods. Pretests and posttests were administered to both groups, and the data were analyzed using descriptive statistics, normality tests, paired sample t-tests, homogeneity tests, and independent sample t-tests with the SPSS version 26 software. The results revealed a significant difference between the control and experimental groups, with the experimental group achieving higher learning outcomes in multimedia subjects. The implications of this study suggest that incorporating flipbook learning media can enhance student learning outcomes in multimedia education. Highlights: Implementation of flipbook learning media significantly improves learning outcomes in multimedia education. Quasi-experimental design allows for comparison between control and experimental groups. Flipbook learning media positively impacts student performance and engagement in Class XII multimedia students. Keywords: Flipbook learning media, learning outcomes, quasi-experimental study, multimedia education, student performance.